2020
DOI: 10.1080/14614103.2020.1777055
|View full text |Cite
|
Sign up to set email alerts
|

Defining Suitability in Mixed Agropastoral Societies: A Case Study from Bactria in Northern Afghanistan

Abstract: This paper explores the concept of suitability within applications of Ideal Distribution Models (IDMs). Specifically, we investigate the effectiveness of single measures of suitability in contexts where diverse local populations practiced a range of subsistence strategies with different environmental requirements and sociocultural consequences. To do so, we draw on legacy survey data from northern Afghanistan, within the historic region of Bactria. This region of Central Asia has a rich history of nomadic past… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…This could also be evidence of resource control by certain populations, forcing larger communities into less suitable locations (e.g., IDD [61][62][63]). Additionally, it has been suggested that where subsistence strategies change, environmental proxies for habitat suitability will require modification [30,98]. This is because the variables associated with "suitability" (and their relative importance) change as subsistence strategies shift (e.g., fishing communities will value marine resources more than pastoralists living inland [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This could also be evidence of resource control by certain populations, forcing larger communities into less suitable locations (e.g., IDD [61][62][63]). Additionally, it has been suggested that where subsistence strategies change, environmental proxies for habitat suitability will require modification [30,98]. This is because the variables associated with "suitability" (and their relative importance) change as subsistence strategies shift (e.g., fishing communities will value marine resources more than pastoralists living inland [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…That is, land-use patterns in the region should not be assumed to be wholly structured by these environmental variables. Perceptions of agricultural suitability may also vary depending on subsistence practices or sociocultural contexts and can themselves be altered through landscape interventions and modifications [73,74]. Given the marked topographic diversity of the region, we expect then that the analysis of elevation and slope should reveal differing and not necessarily overlapping land-use patterns between the past and present.…”
Section: Predictor Variablesmentioning
confidence: 99%